Otimização das propriedades fotocatalíticas de nanocompósitos TiO2-SiO2 sintetizados por tecnologia sol-gel e processo hidrotermal - Hugo Guimaraes Palhares (2019)
Photocatalysis is considered a promising technology for reducing environmental pollution through the photo-oxidative mineralization of organic compounds. Among the photocatalysts currently used, titanium dioxide (TiO2 or titania) is the most used due to its non-toxic nature, water insolubility, expressive thermal and chemical stabilities, low cost and high photoactivity. The catalytic efficiency of TiO2 is influenced by factors such as its crystalline structure and specific surface area. In this work we investigated the effect of hydrothermal treatment and silica addition on the structure and photocatalytic performance of synthesized TiO2-based catalysts. These materials were prepared by combining sol-gel process and hydrothermal treatment, and no templates or surfactants were used in these syntheses. The optimal synthesis conditions were investigated based on the variation of the preparation parameters. Despite obtaining anatase TiO2 crystals without hydrothermal treatment, this one appeared necessary to complete the anatase crystallization to form anatase phase with good structural quality and high photoactivity. The heat treatment step was responsible for the generation of both positive and negative effects in relation to the TiO2 structural properties and its photocatalytic activity. However, in general, it has proved to be advantageous as long as the pore structure, the anatase phase and a high specific surface area were maintained. The addition of silica was then justified, aiming to stabilize the crystalline structure of TiO2 upon heat treatment. The best results were obtained with Si/(Si+Ti) molar ratio of 0.2. An increase in the temperature of the hydrothermal treatment showed to stabilize the structure even more, which corresponded to a higher catalytic performance than the other materials when considering high heat treatment temperatures (i.e., 700 oC). The high photocatalytic efficiency of the synthesized nanocomposites is due to the combined effect of TiO2 photoactivity and SiO2 adsorption capacity. When compared to a commercial sample of TiO2 (Evonik Degussa P25), the best performance of the nanocomposite is observed mainly when it is used in larger quantities.